Fellowship and future career plans for orthopedic trainees: gender-based differences in influencing factors - Abdulaziz Z. Alomar (Heliyon, 2022)
Objective: Understanding gender-based preferences and factors influencing fellowship and subspecialty choice might help maximize gender diversity in orthopedic surgery. This study aims to identify the differences between male and female orthopedic trainees' future career plans. It also examines the factors and determinants that influence selection of fellowship specialties in Saudi Arabia. Methods: This cross-sectional multicenter study recruited orthopedic surgical trainees from multiple training centers. The survey was completed by 270 participants; 20 residents were excluded because they were unsure of their future career interests or preferred fellowships in general orthopedic practice. The participants were either postgraduate orthopedic residents or fellows who already enrolled in postgraduate residency and/or fellowship training program. A total of 201 (80% of 250 participants) were male and 49 (20%) were female. Results: The orthopedic subspecialities and fellowship preferences and their influencing factors varied considerably across genders. Pediatric orthopedics and hand and upper extremity were top sub-specialties preferences among women while arthroscopy and sports medicine, arthroplasty, and trauma were the top preferences among men. Women preferred to practice single subspeciality while men preferred to do multiple fellowships and practiced different orthopedic subspecialities. The expected income, private-sector job opportunities, and hospital needs were the most significant factors influencing subspecialty and future career preferences among men while personal interest and social and family commitments were the most influential factors for women. Conclusions: This study addresses the knowledge gap regarding gender-based subspecialty preferences and the factors influencing them. The results can inform strategy development for addressing women’s needs and interests in orthopedic surgery as well as the shortages of orthopedic surgeons in some subspecialties. Furthermore, these data may assist directors of training centers in analyzing expected future demands on fellowship training programs and addressing the training gap in all subspecialties and career counseling.